Penggunaan Mandeley Dalam Pengelolaan Referensi Pada Penulisan Karya Ilmiah Mahasiswa PG Paud Universitas Widya Gama Mahakam Samarinda - Andi Aslindah; Nur indah Sari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2021)
In managing references for writing scientific papers, sometimes writers are faced with various problems, one of which is in searching for literature, citing references and making a bibliography. This service aims to train the use of the Mendeley application as a reference manager in writing scientific papers for PG-PAUD students at Widya Gama Mahakam University Samarinda. It is hoped that after attending Mendeley's workshop, students can manage bibliography and make citations easily. The target participants in this workshop are all PG PAUD UWGM students but it is mandatory for final semester students who will and are already in the process of preparing their final project (thesis). The method for implementing this Mendeley workshop is online using the Zoom application. The technique of this activity is by presenting the material, giving examples, practice and evaluating the results of the training. The result of this training is that students are able to do citations and create a bibliography automatically on the task of making articles as an evaluation material for this workshop activity.